Características morfogênicas, estruturais e produção de forragem do capim-xaraés submetido a estratégias de manejo - Carvalho, Marcus Vinícius Pavoni de (2011)
The increasing quest for better indexes in animal production systems on pasture, in recent years has contributed to the launch of several cultivars of tropical forage grasses. However issues relating to handling these crops have to be researched, as is the case of xaraés grass, Brachiaria brizantha cultivar released in 2003 and with morphological and physiological characteristics remain poorly known. In this context, the objective was to evaluate the morphogenesis, structure and herbage of grass xaraés subjected to combinations of frequencies and intensities of defoliation. The treatments consisted of combinations of three cutoff heights (35, 55 cm high and when there was the appearance of four leaves per tiller (4F)) and three heights of residues (15, 20 and 25 cm), characterized by the following provisions: 35/15, 35/20, 55/25 and 4F/20. The experimental design was a randomized complete block with five replications. Treatments 35/15, 35/20, 55/25 and 4F/20 resulted in nine, ten, seven and four cuts, respectively. In management strategies with less frequent defoliation, 4F/20, rates of stem elongation and leaf senescence, the leaf size and phyllochron were higher compared to targets who have greater numbers of pluck, 35/20 and 35/20. The leaf elongation rate compared their averages for the entire experimental period was not influenced by the strategies of pluck, recording average of 28.1 mm/day. However, when considering the periods of the year, there was no effect of the goals of defoliation on the rate of elongation. The tiller density showed different patterns of response to the seasons. The total forage production, accumulation rates and the volume density of forage were higher in the strategy that defoliation were less frequent 4F/20, and lower in those with more pluck, 35/15 and 35/20. However, this management more productive greatest participation of the stem and lower leaves. The association 35/15 and 35/20 were those that provided better leaf: stem variable related to quality and herbage intake under grazing condition. In this context, the goal with more frequent defoliation were effective in controlling stem elongation and leaf senescence, variables that correlate negatively with the nutritional value of grass. These strategies have also resulted in lower value phyllochron which characterizes the higher leaf growth allowing the use of pastures more quickly. Thus, it is suggested that the management for the grass-xaraés subject to intermittent or rotational stocking is in the objective function of the production system and should be kept at a height of 35 cm of entry in order to control the elongation of the stalks with output of 15 cm when the system goal is to provide greater gain and output per area of 20 cm when the system goal is to provide greater gain per animal.